2016
DOI: 10.1016/j.jad.2016.04.053
|View full text |Cite
|
Sign up to set email alerts
|

Brain structural anomalies in borderline and avoidant personality disorder patients and their associations with disorder-specific symptoms

Abstract: Background Borderline personality disorder (BPD) and avoidant personality disorder (AvPD) are characterized by hyper-reactivity to negatively-perceived interpersonal cues, yet they differ in degree of affective instability. Recent work has begun to elucidate the neural (structural and functional) and cognitive-behavioral underpinnings of BPD, although some initial studies of brain structure have reached divergent conclusions. AvPD, however, has been almost unexamined in the cognitive neuroscience literature. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 49 publications
(98 reference statements)
0
3
0
1
Order By: Relevance
“…Varios estudios y meta-análisis describen anomalías estructurales y funcionales a nivel cerebral mediante neuroimagen en pacientes TLP, siendo las principales una disminución del volumen de la corteza prefrontal ventromedial y orbitofrontal, una disminución de la corteza cingulada anterior dorsal y disfunción de la amígdala (Carrasco et al, 2012;Denny et al, 2016;Kimmel et al, 2016;Visintin et al, 2016). Los estudios de neuroimagen muestran que existen algunas áreas de superposición y algunas diferencias entre el Trastorno Bipolar y el TLP (Sripada and Silk, 2007).…”
Section: Neuroimagen En Tlpunclassified
“…Varios estudios y meta-análisis describen anomalías estructurales y funcionales a nivel cerebral mediante neuroimagen en pacientes TLP, siendo las principales una disminución del volumen de la corteza prefrontal ventromedial y orbitofrontal, una disminución de la corteza cingulada anterior dorsal y disfunción de la amígdala (Carrasco et al, 2012;Denny et al, 2016;Kimmel et al, 2016;Visintin et al, 2016). Los estudios de neuroimagen muestran que existen algunas áreas de superposición y algunas diferencias entre el Trastorno Bipolar y el TLP (Sripada and Silk, 2007).…”
Section: Neuroimagen En Tlpunclassified
“…Although there is some evidence that suggests a smaller volume of the amygdala in PTSD patients [ 17 ], other studies found no differences in its morphology compared to healthy controls [ 18 , 19 ]. In contrast, amygdala volume is consistently lower in BPD patients relative to healthy controls [ 14 ], while to the best of our knowledge only one study has been conducted in CPD [ 20 ], showing no difference in amygdala volume between patients with avoidant personality disorder and healthy control subjects.…”
Section: Introductionmentioning
confidence: 99%
“…For example in BPD, several studies found significant bilateral volume reductions in the hippocampus compared to HC [21][22][23][24][25][26][27][28] as well as significant bilateral volume reductions in the amygdala. 22,[24][25][26][27] However, there have also been several dissenting studies: three found no significant volume reductions in the hippocampus [29][30][31] and six found no significant reduction in amygdala volumes 29,30,[32][33][34][35] in BPD versus HC.…”
Section: Introductionmentioning
confidence: 99%